Pelatihan Pemanfaatan Fitur Dasar Microsoft 365 Sebagai Media Pembelajaran - Elfira Makmur; Sari, Dessy Ana; Hilda Ashari; Muh. Iswal Burhan; Akhyar Muchtar (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
The use of Microsoft 365 as a learning media is very possible to increase students' understanding in implementing learning media carried out by teachers in the classroom, based on the basic features provided by Microsoft 365 which supports the learning process in the classroom and on assignments. Teachers at SMK Negeri 9 Jeneponto are still not able to make good use of Microsoft 365, such as Microsoft 365 features. It can be seen that there is a lot of interest in using Microsoft 365 but there is a lack of understanding so its use is not yet optimal. This community service activity is carried out by utilizing Microsoft Teams as one of the features in Microsoft 365 which can be used for virtual meets like this PKM implementation method. Problems experienced by partners such as those above can be overcome with PKM solutions in the form of efforts to increase teacher professionalism by providing training on the use of Microsoft 365 as a learning medium. Training on the use of Microsoft 365 as a learning medium in partner schools is considered appropriate so that teachers not only know how to use Microsoft 365, but also practice it.